2004
DOI: 10.1016/s0896-6273(04)00156-4
|View full text |Cite
|
Sign up to set email alerts
|

A Touching Sight

Abstract: Watching the movie scene in which a tarantula crawls on James Bond's chest can make us literally shiver--as if the spider crawled on our own chest. What neural mechanisms are responsible for this "tactile empathy"? The observation of the actions of others activates the premotor cortex normally involved in the execution of the same actions. If a similar mechanism applies to the sight of touch, movies depicting touch should automatically activate the somatosensory cortex of the observer. Here we found using fMRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
185
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 700 publications
(201 citation statements)
references
References 31 publications
(4 reference statements)
14
185
0
2
Order By: Relevance
“…Once the differences in power output between optic flow conditions had been statistically controlled for, RPE remained lower during TT SLOW . This finding is consistent with numerous other studies that, albeit focused on either touch or acute pain, have found an effect of exteroceptive information on the way internal sensory information is perceived (Blakemore, Bristow, Bird, Frith, & Ward, 2005;Johansen-Berg & Lloyd, 2000;Keysers et al, 2004;Longo et al, 2009;Mancini, Longo, Kammers, & Haggard, 2011;McCabe et al, 2008;Schaefer, Flor, Heinze, & Rotte, 2006;).…”
Section: The Effect Of Optic Flow On Perceived Exertionsupporting
confidence: 92%
“…Once the differences in power output between optic flow conditions had been statistically controlled for, RPE remained lower during TT SLOW . This finding is consistent with numerous other studies that, albeit focused on either touch or acute pain, have found an effect of exteroceptive information on the way internal sensory information is perceived (Blakemore, Bristow, Bird, Frith, & Ward, 2005;Johansen-Berg & Lloyd, 2000;Keysers et al, 2004;Longo et al, 2009;Mancini, Longo, Kammers, & Haggard, 2011;McCabe et al, 2008;Schaefer, Flor, Heinze, & Rotte, 2006;).…”
Section: The Effect Of Optic Flow On Perceived Exertionsupporting
confidence: 92%
“…For example, Hutchison et al (1999) and Jackson et al (2005) have shown, for humans, that perceiving pain in others activates the same areas of the brain, such as the anterior cingulate, anterior insula and the cerebellum, that are known to play a role in pain processing. Wickers et al (2003), also for humans, have shown that perceiving facial expressions of disgust in others and experiencing disgust (through exposure to disgusting odorants) both activate the same area of the left anterior insula, while Keysers et al (2004) have shown that the same neural networks are activated both by being touched and by observing the body of someone else being touched. This kind of unmediated, direct form of action and emotion understanding is seen by Gallese (2005) as a basic form of empathy, one which allows animals in possession of mirror mechanisms to establish a meaningful understanding of others and of themselves (see also Preston & de Waal 2002 for a similar argument in relation to primate cognition).…”
Section: Embodied Simulationmentioning
confidence: 96%
“…It is also worth noting that emotions are motorically expressed and, when observed, they may generate motor resonance in the beholder, both at the levels of the face and body. Furthermore, the fact that somatosensory areas, such as SI and SII, show evidence of ES during the first-person experience of touch and its observation in others [44][45][46][47][48] shows how actions and their sensory consequences are multimodally integrated within a variety of brain areas whose unimodal specialization and vocation is clearly challenged, if not totally disproved (for a lengthier discussion of this point, see [98]). …”
Section: Embodied Simulation As Reuse Bodily Self and Bodily Other: mentioning
confidence: 99%